(untitled) (The Agriculturists, 2016)
The experiment was conducted at the field laboratory of the Department of Genetics and Plant Breeding, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during November 2008 to March 2009 to estimate the genetic diversity of exotic and local onion. Ten genotypes of onion were evaluated for 16 characters in a randomized complete block design to study the genetic divergence through multivariate analysis. Ten genotypes formed three clusters. Cluster III contained maximum number of five genotypes. Cluster I and II contained three and two genotypes, respectively. The inter cluster distance was larger than the intra cluster distances. The inter cluster distance was maximum between the cluster II and III (6.336) and minimum between the cluster I and II (3.876). The intra cluster distance in the entire three clusters was more or less low, indicating that genotypes within the same cluster were closely related. Considering clustered distance and cluster mean, the intra cluster distance revealed that the genotypes Indian big (G1) and Patnai pink (G5) from the cluster II and genotypes Taherpuri, Indian medium (G1), Big single bulb (G7), Big double bulb (G8), Small single bulb (G9) and Small double bulb (G10) from the cluster III may be selected as parents for future breeding program. The Agriculturists 2015; 13(1) 26-34